The role of motivation and volition in economic decisions: Evidence from eye movements and pupillometry. (6th August 2019) - Ludwig, Jonas; Jaudas, Alexander; Achtziger, Anja
Abstract: Economic decisions usually involve high stakes, real consequences, and some degree of personal risk. This article explores the impact of motivational and volitional states on economic decision processes in an incentivized lottery choice task. We investigated the patterns of decision time, choice, information search, and pupil dilation dependent on an experimental manipulation of motivation and volition, that is, the deliberative and the implemental mindset. The results indicated that choice preferences in economic decisions were robust and remained unaffected by motivational and volitional states, but decision processes were notably impacted. Decision makers in a deliberative state of mind searched for information more extensively and made slower decisions than the baseline. The implemental mindset was associated with more attention paid to the probability attributes of the gambles relative to the deliberative mindset. Furthermore, we observed that gamble outcomes that entailed no win at all (i.e., zero outcomes) played an important role for information search. These outcomes were largely disregarded in terms of predecisional information search but elicited pupillary responses similar to very high outcome lotteries. These results inform the current debate about the zero effect in risky choice. We also discuss the potential of eye‐tracking studies of risky choice to dissolve ambiguities concerning the contributions of effort and arousal to modulating pupillary response. Implications for theoretical advances in decision research are discussed.